KORUPSI DAN KEMISKINAN DI INDONESIA - Ruhul Aifa; M. Ilhamsyah Siregar (Fakultas Ekonomi dan Bisnis UNSYIAH, 2019)
Abstract This study aims to analyze the relationship between corruption with poverty and a two-way relationship between corruption and poverty. The method used in this research is quantitative analysis method using Autoregressive Distributed Lag (ARDL) model. The data used are time series data from 1996 to 2017. The variables used are Corruption Perception Index (CPI) issued by Transparency International, and the World Bank's Poverty Rate Ratio. The results show that there is a positive and significant correlation between corruption and poverty in Indonesia. The relationship also applies in the short term and in the long run. From the research results also found a strong indication of a two-way relationship between corruption and poverty. The implication of this research is that decision makers in Indonesia need to constantly improve perceptions of Indonesia's corruption by improving oversight, improving the quality of governance and enforcing the law to improve perceptions of Indonesia's corruption. Keywords: Corruption, Poverty, Two-Way Relationship, ARDL, Indonesia